Composição química e bioatividade do óleo essencial das folhas frescas e secas de Melaleuca quinquenervia (Cav.) S. T. Blake (Myrtaceae) - Silva, Francisco dos Santos (2016)
The state of Roraima has a flora with a variety of species in its composition, which are also inserted species from other states and countries where they have great ease of adaptation. It is known that the chemical composition of the metabolites in plants may vary with the form of cultivation, weather and soil. It was the existence of the species Melaleuca quinquenervia (Cav.) S. T. Blake on Campus Paricarana, Federal University of Roraima. This species belongs to Myrtaceae Melaleuca genus, its occurrence is predominantly in Australia, being an important source of essential oils, but there is the existence of M. quinquenervia in southeastern Brazil. A study of the essential oil showed variations in the composition compared to natural species in Australia, and there may be a variation in Roraima. The aim of this study was to investigate the diurnal influence on yield, chemical composition and bioactivities to the essential oil of M. quinquenervia found in Boa Vista-RR. They leave for two periods of the year were collected (wet and dry) at four different times during the day (06:00, 12:00, 18:00 and 00:00). Extractions with fresh and dried plant material occurred during the year 2015. The extraction method used to obtain the essential oil was the hydrodistillation. A significant change was recorded in the income, and the oil extracted in the dry season and at 18:00 had the highest yield (2.05 ± 0.17%) higher than that found in the literature. Of all the extractions performed not there was a qualitative change in the constituents, only quantitative and identified 24 constituents, meeting 9 major constituents, including the 1.8 cineol, viridiflorol, α-terpineol, α-pinene, guaiol, oxide caryophyllene, limonene, myrcene, terpinen-4-ol, respectively. The oil showed 60% of 1.8 cineole chemotype indicating that this species found in Boa Vista-RR belongs to Viridiflorol chemotype as shown in the literature, but was biosynthesized 1,8 cineole. The oils extracted in May and October showed high toxicity 375.74 μg.mL-1 and 359.58 μg.mL-1 respectively to the test with A. salina. The antioxidant activity (DPPH) was presented by the two oils (May and October), but the EC50 was much lower when comparing with the standard of quercetin. The oils were able to inhibit the growth of Bacillus cereus and Salmonella typhimurium. It is concluded that the essential oil of M. quinquenervia obtained in Boa Vista-RR has good percentage for inhibiting biological activity, indicating that this oil can be used for other bioassays.